Me río de la mafia. Los Cubrepileta y la sátira mafiosa en la Argentina - Favero, Bettina Alejandra (Comparative Cultural Studies: European and Latin American Perspectives, 2023)
In this essay, the mafia appears as a cultural object when analyzed from a humorous program broadcast in the 1990s in Argentina. It is Los Cubrepileta, a sketch that was part of Cha Cha Cha starring Alfredo Casero, Fabio Alberti, Diego Capusotto, Vivian El Jaber, Jorge Takashima, Alejandra Flechner, among others. Cha Cha Cha was a crazy, surreal and absurd program broadcast during 1993 and from 1995 to 1997 on América TV. Although the space was never massive, it is interesting to observe and analyze the way in which the sketch dedicated to an Italian family (Los Cubrepileta) parody the mafia with gags, jokes and set phrases inspired by movies and novels as well as the stereotype from the Italian mobster. To this is added another interesting fact, the reproduction of the sketches on YouTube, the visualizations and the comments on them.